Genomic copy number variation associated with clinical outcome in canine cutaneous mast cell tumors - Jark, Paulo C [UNESP]; Mundin, Deborah B.P.; de Carvalho, Marcio [UNESP]; Ferioli, Raquel B. [UNESP]; Anai, Letícia A [UNESP]; Marchi, Fabio A.; Rogatto, Silvia R. [UNESP]; Laufer-Amorim, Renee [UNESP]; Tinucci-Costa, Mirela [UNESP] (Elsevier, 2017)
Mast cell tumors are the most common malignant cutaneous tumors in dogs. Although there are several prognostic factors involved, the clinical and biological behavior of this type of tumor varies greatly, making the best choice of treatment challenging. Molecular techniques can be used to evaluate a large number of genes involved in the neoplastic process and aid in the selection of candidate genes related to prognostic and predicting factors. Identification of the genes associated with tumor development and progression can be performed through the analysis of numerical and structural changes in DNA isolated from tumor cells by array comparative genomic hybridization (aCGH). The aim of this study was to compare copy number variations (CNVs) in cutaneous mast cell tumors of dogs that survived less than six (ST < 6) and > 12 months (ST > 12) from the date of diagnosis. Ten animals were used: four from Group ST > 12 and six from Group ST < 6. Genomic DNA was extracted, and aCGH was performed using Agilent Canine Genome CGH Microarray 4 × 180 (ID-252 552 – Agilent, USA). Data analysis was carried out using Nexus program version 5.0 (Biodiscovery, USA). The group ST > 12 presented 11 ± 3.3 CNVs, while the ST < 6 group presented 85 ± 38.5 CNVs. Regions of loss in PTEN and FAS as well as regions of gains in MAPK3, WNT5B, FGF, FOXM1 and RAD51 were detected in mast cell tumors with shorter survival times, and thus, worst prognoses, allowing for the identification of potential candidate genes for more detailed studies.
Keywords: Canine; Comparative genomic hybridization; Mast cell tumor